A customizable, open-source Winston-Lutz system for multi-target, single isocentre radiotherapy. (1st November 2022) - Oliver, P A K; Wood, T R; Baldwin, L N
Abstract: Objective . To present and share an open-source system (phantom and software) for verifying the targeting accuracy of linac-based, single-isocenter, multi-target radiotherapy. This quality assurance test extends the traditional Winston-Lutz test, which considers a single target located at isocentre. Approach . Plans for a 3D-printed phantom are provided, which can be customized to accommodate various target (BB) positions. Given BB positions and gantry/collimator/couch combinations, the software generates multi-leaf collimator positions to facilitate multi-target Winston-Lutz (MTWL) plan creation. The software determines deviations between detected and expected BB positions on MV images resulting from MTWL plan delivery. BBs are located using a Hough circle detection algorithm, which is modified to favour the detection of circles: (1) having a reasonable size, (2) that are contained within the radiation field, and (3) having reasonable pixel intensities. Validation was performed in two ways: (1) using synthetic data with zero targeting errors and (2) by measuring real linac targeting errors and comparing against results obtained using a commercial system. Main results . Validation using the synthetic data yielded a mean (maximum) absolute discrepancy of 0.11 mm (0.21 mm), which is comparable to the synthetic phantom resolution (0.2 mm). The mean (maximum) absolute discrepancy compared to the commercial system is 0.13 mm (0.43 mm). These values are similar to results obtained with repeated deliveries of the same MTWL plan with the same phantom setup. Both validation tests yield reasonable results and are therefore considered successful. The MTWL test was performed independently by three physicists on two linacs to investigate repeatability, resulting in a mean (maximum) absolute discrepancy of 0.14 mm (0.51 mm) among the various attempts. Significance . Successful completion of this quality assurance test, using our customizable and open-source system, provides confidence that multi-target, single isocentre radiotherapy treatments can be delivered with sufficient geometric accuracy according to the chosen tolerance level.